2012
DOI: 10.1159/000345509
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid-Induced Endothelial Dysfunction Is Associated with Mitochondrial Alterations and Decreased Intracellular ATP Concentrations

Abstract: Background/Aims: Endothelial dysfunction is associated with mitochondrial alterations. We hypothesized that uric acid (UA), which can induce endothelial dysfunction in vitro and in vivo, might also alter mitochondrial function. Methods: Human aortic endothelial cells were exposed to soluble UA and measurements of oxidative stress, nitric oxide, mitochondrial density, ATP production, aconitase-2 and enoyl Co-A hydratase-1 expressions, and aconitase-2 activity in isolated mitochondria were determined. The effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
215
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 273 publications
(224 citation statements)
references
References 48 publications
6
215
1
2
Order By: Relevance
“…High levels of UA were previously found to induce mitochondrial dysfunction, which may lead to excess ROS generation. This suggested that mitochondrial uncoupling decreases the synthesis of ATP via oxidative phosphorylation (Sánchez-Lozada et al, 2012). Therefore, we hypothesized that the decrease in ATP content in the hepatocyte mitochondria was correlated with mitochondrial uncoupling promoted by UA-induced ROS.…”
Section: Discussionmentioning
confidence: 95%
“…High levels of UA were previously found to induce mitochondrial dysfunction, which may lead to excess ROS generation. This suggested that mitochondrial uncoupling decreases the synthesis of ATP via oxidative phosphorylation (Sánchez-Lozada et al, 2012). Therefore, we hypothesized that the decrease in ATP content in the hepatocyte mitochondria was correlated with mitochondrial uncoupling promoted by UA-induced ROS.…”
Section: Discussionmentioning
confidence: 95%
“…18 Uric acid is known to stimulate MCP-1/CCL2 and oxidative stress in vascular smooth muscle cells 20,21 and endothelial cells. 22,23 Experimentally, uric acid has been shown to activate the renin angiotensin system, induce microvascular disease, alter renal autoregulation, and increase glomerular hydrostatic pressure. 18,24 Fructose can also increase the expression of intercellular adhesion molecule-1 in vascular endothelial cells throughout the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that UA-induced endothelial dysfunction is associated with decreased intracellular ATP concentrations and mitochondrial alterations (24). Therefore, the present study evaluated whether LA treatment affects mitochondrial mass and function in the process of hyperuricemia.…”
Section: La Rescues Vascular Endothelial Cell Mitochondrial Mass Andmentioning
confidence: 93%